Analysis of Psychoanalytic Therapy Intervention: for Individuals with Post Traumatic Stress Disorder (PTSD) - Burhanuddin, Rohmat; Casmini, Casmini (World Psychology, 2024)
Post Traumatic Stress Disorder (PTSD) is a psychiatric disorder that occurs after an individual experiences or witnesses a traumatic event that threatens their life or physical integrity. This study aims to analyze psychoanalytic therapy interventions for individuals with PTSD and assess their effectiveness in reducing PTSD symptoms and improving their quality of life. Psychoanalytic therapy is an interesting approach in helping individuals with PTSD by understanding the psychological conflicts that underlie symptoms and emotional problems. This research method uses a literature review of individuals with PTSD who have received psychoanalytic therapy. The data obtained were then analyzed to identify important themes related to the therapy process and the psychological changes that occurred. The results of the analysis showed that psychoanalytic therapy had a positive effect in reducing PTSD symptoms in individuals. The intervention provided an opportunity for them to explore and understand the root emotional issues related to the trauma, which in turn helped them face and cope with the psychological impact of the traumatic event. The therapeutic process also contributes to improved quality of life, deeper self-understanding and better adaptability.